AB1075 Argentinian Register of BIOLOGICS Treatments (BIOBADASAR). Results. (10th June 2014) - Gomez, M.G.; de la Vega, M.C.; Casado, G.; Exeni, I.; Gobbi, C.; Quintana, R.; Pons Estel, B.; Bertoli, A.; Miretti, E.; Saurit, V.; Paira, S.; Mussano, E.; et al.
Abstract : Background: BIOBADASAR (Argentinian Registry for Adverse Events with Biologic Treatments in Rheumatology) began in August 2010.The importance of the register is to show local data as, probably, it could be different from other registries. Objectives: The objective is to communicate data from BIOBADASAR, Argentine Registry of Adverse Events (AE) caused by the use of biological agents in Rheumatology Methods: All Patients with rheumatic diseases that require biologic treatment and control patient, not treated with biological agents, were included in the database from 32 participating sites in Argentine. Three areas were studied: patient features, treatment assigned and adverse events (AE). Loading data began in August 2010 and closed for this analysis, in August 2013. The Infostat software was used to for statistical analysis. Incident rates, relative risk and incidence density for each adverse event were calculated. Results: 2356 patients were included (1277 cases and 1079 controls) with 2940 treatment courses. Mean age was 54 years (range 1 to 90), 1862 (79%) were females and 494 were men (21%). 1107 patients (58%) were treated with biologic agents (cases) and 802 (42%) were controls. 1829 patients had rheumatoid arthritis and 218 psoriatic arthritis among the main diagnoses. The median time of disease duration was 9.81 years and 12.59 for controls and cases respectively. The most frequent biologic used was etanercept (46.7% of treatments) with a median treatment survival of 31 months followed by adalimumab with 23.6% of the treatments and a median survival of 26.4 months. The most frequent cause of treatment interruption for cases was inefficacy (30%) followed by adverse event (26%). The incidence of serious adverse events was 37/1000 patients years in the biologic group vs. 5/1000 patients years in the control group (RR 7.44; CI 517-10.7; p<0.05). The most common AE was infection with a RR of 1.66 (CI 1.38-2.0; p<0.05). Within infections pneumonia had a RR of 29.31 (CI 9.21-93.25; p<0.05), herpes zoster: RR 4.12 (CI 2.08-8.15; p<0.05) and cutaneous infections a RR of 7.21 (CI 3.89- 13.36; p<0.05). Tuberculosis had a RR of 4.53 (CI 0.472-43.56). Tumoral diseases had a RR of 2.82 (CI 1.61-4.95; p<0.05). Conclusions: This is the third BIOBADASAR report showing the reality of biological treatments in Argentina. Patients in Latin American countries show some differences with other countries even with the same treatments due to differences in regional diseases, vaccination or tolerability to pathogen agents. Bias might be present and they would be minimized with tight monitoring and longer follow up time. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2530